Why deemed and private universities are lagging in publishing their research online with India’s national repository? - Kumar, Atul (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. The Indian national online PhD theses repository, “Shodhganga,” published approximately 584,000 theses. The top 10 universities that contributed approximately 25% of the total were all central and state universities. In contrast, the number of theses contributed by deemed and private universities was comparatively limited. This study explored the factors contributing to the limited contributions from deemed and private universities and proposed strategies to enhance their engagement in research dissemination. Design/Methodology/Approach. To obtain a comprehensive understanding of the subject matter, 15 research experts from deemed and private universities in India were interviewed. A qualitative data analysis methodology was employed. Thematic analysis was employed to extract common views. Results/Discussion. The expert group posited that faculty members from deemed and private universities exhibited a greater propensity for academic social networks such as ResearchGate and Academia.edu. The national repository should provide feedback features analogous to those offered by ResearchGate and Academia.edu. It was anticipated that a substantial online research publication would be made available to the public if the deemed and private universities enhanced their contributions. Conclusions. The Indian national repository, Shodhganga, achieved notable growth in its publication of PhD theses, with a total of 584,000 records currently available. However, the repository’s development revealed some concerns regarding the inclusivity of institutional representation. The majority of contributions originated from government-owned state and central universities, suggesting an imbalance in institutional engagement. Deemed and private universities contributed a comparatively smaller share of theses to the repository. This study made a novel contribution to the field by highlighting problems of national repositories that may see uneven growth. To ensure that the research shared was representative of all the stakeholders, they ought to work toward inclusive growth.